Desenvolvimento de implante ortopédico para o tratamento da fratura de Hoffa utilizando tecnologia CAD/CAE/CAM: proposta de um novo método de fixação - Mendonça, Celso Júnio Aguiar (2024)
Introduction: The coronal fracture of the femoral condyle (Hoffa’s fracture) has an intraarticular location, involving a complex anatomy, little blood supply, coronal fracture line with inherent instability that make this fracture present great difficulty in achieving bone consolidation with good functional results. Current surgical techniques recommend stabilization of most of these fractures using a plate and screw. Objective: the objective of this study was to design, implement through Additive Manufacturing (AM) in titanium alloy (Ti6Al4V), simulate and analyze using the Finite Element Method (MEF), test, validate through static mechanical testing of compression and describe the entire technological development process of an orthopedic implant model (H-shaped plate) specific for the treatment of Hoffa fractures. Materials and Methods: A clinical case of a patient undergoing surgical treatment for nonunion of a lateral Hoffa fracture inspired the study. From the Computed Tomography (CT) scan in DICOM format, the creation and modeling of the 3D bone model was carried out using Invesalius, Meshmixer and Blender software. The modeling of orthopedic implants was carried out using SolidWorks software. From then on, virtual surgical planning was carried out with anatomical reduction of the fracture with the choice and implant positions. The Ansys software was used to perform numerical simulation by FEM of the types of fracture fixation. The domains were discretized, the mechanical and tribological properties were determined, the boundary conditions were defined, and force was applied in accordance with literature data. Six domains (called system) were defined according to the types and combinations of implants used in Hoffa fracture fixation. To analyze the mechanical stability of the systems, four points were defined on the fracture surface of the virtual bone model to measure the relative displacement and measure the maximum von Mises stress of the implants. The evaluation of the simulation results by FEM was carried out with visual analysis of the color gradient of bone displacement and implant tension. A quantitative analysis of measurements of the bone displacement of the distal fragment, the relative displacement of the points and the maximum von Mises tension of the implants was carried out. AM of polyamide bone models was performed with Select Laser Sintering (SLS) technology. The AM of the plates using Ti6Al4V was carried out using Electron Beam Melting (EBM) technology. It was found that this technology was not accurate in the AM of the screws. These were then manufactured with subtractive manufacturing (MS) using grade 23 Ti6Al4V bars. The 3D printed plates underwent surface post-processing with laser scanning and thread milling. The bone models were subjected to fixation with the manufactured implants and then the bone-implant systems were subjected to static mechanical compression testing (MT) in a universal testing machine. Results: The FEM analysis showed that the systems that were fixed with the H-plate presented the smallest relative displacement of the distal bone fragment when subjected to a load of 1,357.70 N. The results of the mechanical test of the specimens showed greater rigidity of the osteosyntheses with the system subjected to fixation with interfragmentary screws including the H-plate. Conclusion: The H-plate presents the greatest osteosynthesis stiffness with the smallest relative displacement of the distal bone fragment compared to traditional osteosynthesis methods for this type of fracture during FEM simulation and presents greater stiffness compared to three fixation methods and stiffness similar to two traditional fixation methods during the Mechanical Test.